Occupational chemical exposures in pregnancy and fetal growth: evidence from the Born in Bradford Study - Shirangi, Adeleh; Wright, John; Blair, Eve M; McEachan, Rosemary RC; Nieuwenhuijsen, Mark J (Scandinavian Journal of Work, Environment & Health, 2020)
' ' OBJECTIVES ': 'This prospective birth cohort study evaluated the effect of occupational exposure to endocrine disrupting chemicals (EDC) during pregnancy on inadequate fetal growth as measured by small-for-gestational age (SGA) and inadequate fetal growth measured by percentage of optimal birth weight (POBW). The study also identified the maternal characteristics associated with an increased risk of exposure to EDC. ' ' METHODS ': 'We studied 4142 pregnant women who were in paid employment during pregnancy and participated in a population-based, prospective 2007–2011 birth cohort study, the Born in Bradford Study, with an estimated participation of 80%. Job titles were coded at 26–28 weeks` gestation at a 4-digit level according to 353 unit groups in the 2000 UK Standard Occupational Classification. They were then linked to expert judgment on exposure to each of ten EDC groups as assessed through a job exposure matrix (JEM). We performed generalized estimation equation modelling by a modified Poisson regression to assess the risk of POBW and SGA associated with an increased risk of chemical exposures. ' ' RESULTS ': 'The frequency of POBW<85 significantly increased for mothers exposed to pesticides [adjusted risk ratio (RRadj) 3.72, 95% confidence interval (CI) 1.40–9.91] and phthalates (RRadj 3.71, 95% CI 1.62–8.51). There was a 5-fold increase risk of SGA for mothers exposed to pesticides (RRadj 5.45, 95% CI 1.59–18.62). Veterinary nurses and horticultural trades were most frequently associated with exposure to pesticides while hairdressers, beauticians, and printing machine minders were associated with phthalates. ' ' CONCLUSION ': 'Maternal occupational exposure to estimated concentrations of pesticides and phthalates is associated with impaired fetal growth.
Keywords: Born in Bradford Study; chemical exposure; EDC; endrocrine disrupting chemical; epidemiology; exposure; fetal growth; maternal characteristic; occupational chemical exposure; percentage of optimal birth weight; pregnancy; prospective cohort; still birth